A sociolinguistic analysis of Coloured gay men's linguistic repertoires and the intersections of Kaaps and Gayle as performative linguistic varieties - Plato, Tasneem (Stellenbosch : Stellenbosch University, 2021)
Thesis (MA)--Stellenbosch University, 2021.